(untitled) (Journal of Global Accounting, 2024)
The study evaluated the effect of corporate diversification on value of conglomerate listed companies in Nigeria. The specific objective was to ascertain the effect of product diversification, subsidiary diversification, regional diversification and sector diversification on the Tobin’s Q of listed conglomerates in Nigeria. Ex-post facto research design was adopted in the study. The population of the study is six (6) listed firms under the Nigerian conglomerate sector. Purposive sampling was used in selecting the sample size of five (5) conglomerates that were listed from 2012 to 2023. Secondary data were collected from the annual reports of the sampled conglomerates for a twelve year period that spanned from 2012 to 2023. The regression model was validated using test of heteroskedasticity, normality, and multicollinearity. Hypotheses of the study were tested using Robust Least Square regression analysis to account for the outliers observed in the data. The findings revealed the following: product diversification has a significant negative effect on corporate value of listed conglomerates in Nigeria (p-value = 0.0000); subsidiary diversification has a significant positive effect on corporate value of listed conglomerates in Nigeria (p-value = 0.0000); regional diversification has a significant positive effect on corporate value of listed conglomerates in Nigeria (p-value = 0.0000); sector diversification has a significant negative effect on corporate value of listed conglomerates in Nigeria (p-value = 0.0072). In conclusion, not all forms of diversification contribute positively to the value of conglomerates in Nigeria. While subsidiary and regional diversification strategies appear to enhance corporate value by leveraging specialized management and geographical expansion, product and sector diversification may introduce inefficiencies and strategic misalignments that diminish firm value. The study recommends that to mitigate the negative impact of product diversification, the Board of Directors and Senior Management should prioritize core competencies and streamline product lines by discontinuing underperforming or non-core products and focusing on areas where the conglomerate has a competitive advantage..